Safe Salinity Levels for Irrigation of Two Ornamental Crops: Hibiscus and Mandevilla: AE574/AE574, 6/2022 - Her, Young Gu; Vassilaros, E. Vanessa (EDIS, 2022)
This publication introduces the findings from a recent study conducted to find safer levels of water salinity in the irrigation of two economically important foliage crops: Hibiscus rosa-sinensis and Mandevilla splendens. Written by Young Gu Her and E. Vanessa Vassilaros, and published by the UF/IFAS Department of Agricultural and Biological Engineering, June 2022.